Ökonomien der Geschlechter. (Verlag Barbara Budrich, 2007)
In this volume, connections between education, power and economy are discussed and problematized from a gender-theoretical perspective. In view of the observed change of systems in politics, science, culture and the social sphere, this thematic field is discussed in various contributions from new theoretical perspectives. The volume contains contributions on the philosophy of education as well as historical and sociological studies that systematically examine one or more facets of these interrelationships from a gender-theoretical perspective.